2006
DOI: 10.1529/biophysj.105.060442
|View full text |Cite
|
Sign up to set email alerts
|

Change in Rigidity in the Activated Form of the Glucose/Galactose Receptor from Escherichia coli: A Phenomenon that Will Be Key to the Development of Biosensors

Abstract: Recently a periplasmic glucose/galactose binding protein, GGRQ26C, immobilized on a gold surface has been used as an active part of a glucose biosensor based on quartz microbalance technique. However the nature of the glucose detection was not clear. Here we have found that the receptor protein film immobilized on the gold surface increases its rigidity when glucose is added, which explains the unexpected detection signal. To study the rigidity change, we developed a new fast and simple method based on using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…Atomic force microscopy (AFM) is a quite versatile tool to detect physical presence of molecules on the cell surfaces (18)(19)(20)(21), in particular, the pericellular coat (22)(23)(24)(25)(26). It is due to a broad range of forces the AFM probe can exert on the sample surface.…”
Section: Introductionmentioning
confidence: 99%
“…Atomic force microscopy (AFM) is a quite versatile tool to detect physical presence of molecules on the cell surfaces (18)(19)(20)(21), in particular, the pericellular coat (22)(23)(24)(25)(26). It is due to a broad range of forces the AFM probe can exert on the sample surface.…”
Section: Introductionmentioning
confidence: 99%
“…Enteric bacteria (1) use glucose/galactose binding protein (GGBP) in separate pathways to actively transport methylgalactosides across the cell membrane (2,3) and to chemically sense them as part of the swimming regulatory scheme (1,4,5). In addition to the fundamental importance of GGBP in the molecular and cellular biology of enteric bacteria, the potential to exploit GGBP for glucose detection has motivated extensive study (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Crystallographic (16) and bulk steady-state (6,7,(17)(18)(19)) studies of GGBP have investigated its binding of glucose, which is usually described by a single (5)(6)(7)19) binding constant, though some studies have suggested otherwise (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…It allows measurement of the elasticity (rigidity) of the surfaces [e.g. of cells and molecules (17)(18)(19)(20)], friction between the AFM probe, and the surface of study (21)(22)(23).…”
mentioning
confidence: 99%